A Heuristic for Wearable Virtual Reality Educational Applications - Rahimah, Mat (Wiley, 2025)
Students frequently encounter difficulties in grasping abstract concepts within the education process, particularly in subjects like science. To address the diverse learning needs of students, educational institutions globally are increasingly adopting advanced technology-based tools. Virtual Reality (VR), transitioning from its origins in gaming, has emerged as a significant tool in education, offering engaging and immersive learning experiences. The usability of VR educational applications is paramount as it directly influences student satisfaction, motivation, and learning outcomes, especially in challenging subjects. However, a notable gap exists in the lack of established guidelines for evaluating the usability of virtual reality educational applications. This research aimed to develop and validate a comprehensive heuristic checklist for evaluating the usability of wearable VR educational applications (WVREA). Employing an eight-step methodology, the study involved expert judgment from academics and industry practitioners (n=25) for the efficacy assessment of the heuristics, followed by heuristic evaluations conducted by academics and industry practitioners (n=15) and schoolteachers (n=15). The findings indicated that the developed checklist effectively identified and addressed key usability issues, with no further heuristics deemed necessary. Positive feedback from HCI experts, VR specialists, and schoolteachers confirmed the effectiveness of the revised heuristics in addressing usability concerns. This research demonstrates the potential of the developed heuristic checklist to serve as a standard assessment tool for WVREA usability. Ultimately, this study lays a crucial foundation for establishing standardised usability practices for WVREA, thereby facilitating the creation of more user-centred and effective VR educational experiences. Keywords: Wearable Virtual Reality (WVREA), VR education, VR Usability Evaluation, Usability Heuristics, and Standardised Evaluation Practices.